Sunday

April 20, 2014

April 20, 2014

Posted by **Joe** on Sunday, January 31, 2010 at 7:25pm.

F(0) = 0

f(-1)= 1

f(2)= 45

is this right?

- Math -
**jh**, Sunday, January 31, 2010 at 7:32pmf(0) = 0 is right

f(-1) = 10

f(-1) = 5(-1)^2 - 5(-1)

= 5(1) - (-5)

= 5 + 5

= 10

f(2) = 10

f(2) = 5(2)^2 - 5(2)

= 5(4) - 10

= 20 - 10

= 10

HOPE THIS HELPS!!

**Related Questions**

algebra - find the indicated outputs for f(x)=3x^2-5x I get f(0)=0 f(-1) = 1 f(2...

Math - Find the indicated outputs for f(x)=5x^2-2x. f(0)= f(-1)= f(2)=

Math - Find the indicated outputs for f(x)= 5x^2-2x The 2 after the ^ is an ...

algebra - find the indicated outputs for f(x = 3x^2 -5x f(0)= f(-1)= f (2)=

math - Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated ...

Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)= 4x^2- 5x= f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)= 4x-5x= f(0)= f(-1)= f(2)=

Algebra 1 - Find the indicated outputs for f(x)=4x(2)-5x f(0)=? f(-1)=? (f(2)=?

Math - 1.Write the equation 5x+y-2=0 in normal form. 5x+y-2=0 5x+y=2 (add two to...